The Ca2+‐activated Cl− channel, ANO1 (TMEM16A), is a double‐edged sword in cell proliferation and tumorigenesis. (18th March 2014) - Qu, Zhiqiang; Yao, Weicheng; Yao, Ruyong; Liu, Xiangping; Yu, Kuai; Hartzell, Criss
Abstract Since anoctamin 1 ANO1 (TMEM16A) was found to be a molecular component of Ca2+‐activated Cl− channels, its role in tumorigenesis has gained attention at a fast pace. ANO1 overexpression frequently occurs in the cancer tissues along with 11q13 chromosome amplification. Poor prognosis of many types of cancers has been closely correlated with ANO1 gene amplification and protein overexpression. ANO1 is now considered an excellent biomarker for certain cancers. Recent research suggests that it is the channel function of ANO1 that is involved in the tumorigenesis. However, how the overexpression of the functional ANO1 causes malignant transformation of tissues via signaling pathways, for example, MAPK remains to be investigated. Clarification of the reasons in future will avail to make ANO1 as a target for cancer treatment.